Transfer and Adaptation of Global Policies: The Dynamics of Implementing Child-Friendly Cities in Padang - Utami, Maulidya Alfi; Yusran, Rahmadani (Al-Qalam Institue, 2025)
The Child Friendly City (CFC) policy is a global initiative adopted by various countries, including Indonesia, to ensure children’s rights and protection in urban areas. Padang City has implemented this policy through local regulations and five strategic programs. However, achieving the “CFC Primary Category” administratively does not fully reflect success in improving children's quality of life at the local level. This study explores the dynamics of policy transfer and adaptation of the CFC agenda from global and national levels to Padang, focusing on local actors, adaptation forms, and implementation challenges. Using a qualitative approach and the policy transfer framework, data were collected through interviews, document analysis, and field observations. The findings highlight five key barriers to effective adaptation: unequal child participation, low parenting literacy, stigma toward counseling, limited resources, inadequate school preparedness, and weak digital literacy. The study suggests that the policy transfer process has been partial, lacking value internalization and institutional change. The implications for educational management include integrating local educational policies with child protection efforts, enhancing teacher training, and fostering greater community involvement to address these challenges.